Audio Describing Sound – What Sounds are Described and How? : Results from a Flemish case study - Vercauteren, Gert; Reviers, Nina (Journal of Audiovisual Translation, 2022)
Given that the aural meaning-making channels are the main channels that people with sight loss have access to when processing audiovisual products, it is striking that hardly any research has been done on how dialogues, music, and sound effects are integrated in audio description (AD). A possible explanation is the lack of conceptual, theoretical, and methodological frameworks to systematically analyse sound. In the present article we study whether insights from film studies, multimodality research and audionarratology can be used to study sound in AD. After an overview of the state of the art, we present a case study that was carried out within the context of two master’s dissertations and for which an analytical framework for sound descriptions was designed and tested on different scenes from the Flemish film Loft (Van Looy, 2008). In addition to testing the validity of the framework, we wanted to obtain some concrete insights into what types of sounds were described and what narrative position and functions they occupied. On the one hand, the analysis shows AD usually renders the sounds that are the most prominent and most easily recognized. On the other hand, the analysis also shows that although the framework for the analysis clearly has its merits and can provide valuable insights, determining the narrative functions of sounds remains difficult. Therefore, the article ends with various new research questions and a clear plea for more research in this uncharted territory. Lay Summary When people with sight loss listen to an audiovisual product like a film or series, they mainly follow the story based on the sounds, such as dialogues, music, sound effects and the audio description track. It is, therefore, surprising that researchers have not paid a lot of attention to understanding how sounds complement the audio description in telling the story. One reason may be that researchers lack the necessary methods and theory to study sounds scientifically. In this paper, we try to develop this knowledge, by combining insights from different disciplines, such as film studies, multimodality research and audionarratology to create a framework for sound analysis in AD. Together with two Master students, we applied the framework to a case study, namely the analysis of the Flemish film Loft, directed by Erik Van Looy in 2008. The aim of this project was to test the methods we propose for this analysis. But we also wanted to find out what types of sounds are usually audio described and what their narrative contribution is - how they help build the story that is told in the film. Our analysis shows that AD usually renders the sounds that are the most prominent and most easily recognized. The analysis also shows that it is difficult to understand the narrative contribution of sounds, though, with the current scientific frameworks that we have. Therefore, the article ends with various new research questions and a clear plea for more research in this domain.